The impact of wheat cultivar mixtures on virulence dynamics in Zymoseptoria tritici populations persists after interseason sexual reproduction. (17th May 2022) - Orellana‐Torrejon, Carolina; Vidal, Tiphaine; Saint‐Jean, Sébastien; Suffert, Frédéric
Abstract: This study follows on from a previous study showing that binary mixtures of wheat cultivars affect the evolution of Zymoseptoria tritici populations within a field epidemic from the beginning (t1) to the end (t2) of a growing season. Here, we focused on the impact of interseason sexual reproduction on this evolution. We studied mixtures of susceptible and resistant cultivars (carrying Stb16q, a recently broken‐down resistance gene) in proportions of 0.25, 0.5 and 0.75, and their pure stands. We determined the virulence status of 1440 ascospore‐derived strains collected from each cultivar residue by phenotyping on seedlings. Virulence frequencies in the ascospore‐derived population were lower in mixtures than in pure stands of the resistant cultivar, especially in the susceptible cultivar residues, as at t2, revealing that the impact of mixtures persisted until the next epidemic season (t3). Surprisingly, after sexual reproduction the avirulence frequencies on the resistant cultivar residues increased in mixtures where the proportion of the susceptible cultivar was higher. Our findings highlight two epidemiological processes: selection within the pathogen population between t1 and t2 driven by asexual cross‐contamination between cultivars (previous study) and sexual crosses between avirulent and virulent strains between t2 and t3 driven by changes in the probabilities of physical encounters (this study). Mixtures therefore appear to be a promising strategy for the deployment of qualitative resistances, not only to limit the intensity of Septoria tritici blotch epidemics, but also to reduce the erosion of resistances by managing evolution of the pathogen population at a pluriannual scale. Abstract : The impact of wheat cultivar mixtures on Z. tritici populations persists after interseason sexual reproduction. Mixtures are a promising strategy to reduce the erosion of resistance by managing evolution of the pathogen population.